The Language of Synchronous and Asynchronous Interactions of EMC - Madoyan, Narine (Armenian Folia Anglistika, 2013)
The article examines the peculiar features of EMC, namely through the comparison of the linguistic and paralinguistic expressions of e-mails and chats. The analysis of the factual material reveals that the language of e-mails possesses certain similarities (syntactic, semantic, structural) with written speech. The abovementioned similarities cannot be viewed as standard practice since the language of e-mails often contains certain elements typical of both written and oral speech. The language of chats, on the other hand, can be defined as a form of internet expression of oral speech. It is noteworthy, that the emotions and feelings of the participants are expressed through a special sign system.